From oxidative stress to inflammation: redox balance and immune system - Lauridsen, Charlotte (Poultry science, 2019)
Important intestinal diseases in young pigs and chickens, such as diarrhea and enteritis, may be associated with oxidative stress and inflammatory reactions. Especially enteric infectious diseases of weaned pigs and broiler chickens are responsible for a high antibiotic consumption, and there is a major request for alternative strategies to enhance animal disease resistance and robustness. The aim of this presentation was to address the role of oxidative stress and inflammation to combat infectious pathogens, and to elucidate how the reactive processes will contribute to normal immune defense mechanisms of the animal. Furthermore, factors that can enhance oxidative stress (e.g., intensive production, heat stress, polyunsaturated fatty acids, and impaired fat quality), uncontrolled inflammatory reactions (e.g., high ratio of n-6 and n-3 in cellular membranes), and limited immune development (such as micronutrient deficiency) are addressed. In addition, the presentation reviews how micronutrient supplementation during critical phases can support a normal immune system and modulate resistance to infectious diseases of pigs and poultry. The mechanisms concern especially modulation of signal transduction in leukocytes (fat-soluble vitamins and fatty acids) and protection against immunopathology, as exerted by the antioxidative vitamins and selenium. Substantial advances in optimized gut health could be expected by increasing our understanding on how to foster or inhibit production of reactive oxygen species and inflammatory reaction; the relation to enteric pathogens, and how to monitor the effect of disease prevention in farm animals by the use of antioxidant therapy and antibacterial feed components.